Volatile fatty acids and methane production in dairy cow ration based on protein-energy synchronization index with a meals protein source - Afduha Nurus Syamsi; Lastriana Waldi (Faculty of Animal Science, Universitas Brawijaya, 2021)
The study was aimed to examine the production of volatile fatty acids (VFA) and methane (CH4) in rations based on protein-energy synchronization index (PES) using different meals protein sources (MPS). The study was conducted experimentally with in vitro techniques. The factorial completely randomized design (CRD) was used to examine six types of treatment rations originating from a combination of 3 PES index and two types of MPS, each repeated four times so that there were a total of 24 experimental units. The results showed that the interaction of the SPE index had no significant effect on the production of partial VFA, but had a significant effect on the acetate: propionate (A: P) ratio and CH4 production. The analysis of honestly significant different (HSD) results showed that the lowest A: P ratio and CH4 were found in R1. The orthogonal test shows that coconut and soybean meal had a quadratic effect on the A: P ratio and CH4. It concluded that the best PES index to optimize VFA and minimize CH4 production was at the index 0.6-0.61 with soybean meal as protein source supplementation.